Syn- and post-eruptive erosion, gully formation, and morphological evolution of a tephra ring in tropical climate erupted in 1913 in West Ambrym, Vanuatu - Nemeth K; Cronin SJ (Elsevier, 2007)
Syn- and post-eruptive erosion of volcanic cones plays an important role in mass redistribution of tephra over short periods. Descriptions of the early stages of erosion of tephra from monogenetic volcanic cones are rare, particularly those with a well-constrained timing of events. In spite of this lack of data, cone morphologies and erosion features are commonly used for long-term erosion-rate calculations and relative age determinations in volcanic fields. This paper offers new observations which suggest differing constraints on the timing of erosion of a tephra ring may be operating than those conventionally cited. In 1913 a tephra ring was formed as part of an eruption in west Ambrym Island, Vanuatu and is now exposed along a continuous 2.5 km long coastal section. The ring surrounds an oval shaped depression filled by water. It is composed of a succession of a phreatomagmatic fall and base-surge beds, interbedded with thin scoriaceous lapilli units. Toward the outer edges of the ring, base-surge beds are gradually replaced in the succession by fine ash-dominated debris flows and hyperconcentrated flow deposits. The inter-fingering of phreatomagmatic deposits with syn-volcanic reworked volcaniclastic sediments indicates that an ongoing remobilisation of freshly deposited tephra was already occurring during the eruption. Gullies cut into the un-weathered tephra are up to 4 m deep and commonly have c. 1 m of debris flow deposit fill in their bases. There is no indication of weathering, vegetation fragments or soil development between the gully bases and the basal debris flow fills. Gully walls are steep and superficial fans of collapsed sediment are common. Most gullies are heavily vegetated although some active (ephemeral) channels occur. These observations suggest that the majority of the erosion of such tephra rings in tropical climates takes place directly during eruption and possibly for only a period of days to weeks afterward. After establishment of the gully network, tephra remobilisation is concentrated only within them. Therefore the shape of the erosion-modified volcanic landform is predominantly developed shortly after the eruption ceases. This observation indicates that gully erosion morphology may not necessarily relate to age of such a landform. Different intensities of erosion during eruption (related to water supply or rainfall) are probably the major influence on gully spacing, modal depth and form. Longer-term post-eruption processes that could be indicators of relative age may include internal gully deepening (below basal debris flow fill sediments) and possibly widening and side-slope lowering due to undercutting and side-collapse. © 2006 Elsevier B.V. All rights reserved.
Keywords: Maar; Scoria; Base surge; Debris flow; Mud flow; Gully; Ambrym; Tephra ring